Local financial development, access to credit and SMEs' performance: Evidence from Bangladesh - Monzur Hossain; Naoyuki Yoshino; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2018)
This paper tests whether local financial development matters for SMEs' growth performance. We develop a theoretical model framework based on banks' and firms' profit-maximizing behavior that critically hinges upon credit default risk ratio. We argue that an expansion of branch network would increase competition among banks to find good borrowers, which will likely to reduce credit default risk of banks. Our empirical analysis based on the theoretical framework confirms that decreasing credit default risk would decrease interest rates and therefore increases the demand for loans. Thus, bank branch growth has positive and significant impact on firms output growth and productivity. For the empirical analysis, we have used 3 groups of data of Bangladesh including i. firm level data; ii. financial development data; and iii. subdistrict level geographical data. The main policy implication of this paper is that local financial development, particularly bank branch network expansion at subdistrict level could ease access to finance and thereby improve performances of SMEs in developing countries.
Keywords: O16; L25; 330; small and medium enterprise (SME); local financial development; bank branch network; firm performance; Bangladesh